1998
DOI: 10.1046/j.1365-2141.1998.00901.x
|View full text |Cite
|
Sign up to set email alerts
|

The expression of co‐stimulatory molecules and their relation‐ ship to the prognosis of human acute myeloid leukaemia: poor prognosis of B7‐2‐positive leukaemia

Abstract: Summary.We examined the expression of co-stimulatory molecules on leukaemic cells of 52 adult patients with acute myeloid leukaemia (AML) (34 men and 18 women) and analysed the relationship between these expressions and the patient's prognosis. B7-1 was not expressed in any of the 23 patients investigated, whereas B7-2 was expressed in 26/52 patients (50·0%). B7-2 was expressed in all AML patients with monocytic morphology (M4 or M5) and in 16/42 cases without monocytic morphology. CD54 was expressed in 28/ 37… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
40
1

Year Published

1999
1999
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(52 citation statements)
references
References 28 publications
11
40
1
Order By: Relevance
“…Many haematological malignancies express B7 constitutively 8 and in both AML and multiple myeloma (MM) patients membrane expression of CD86 is in fact associated with a considerably poorer prognosis. 9,10 The levels of mCD86 in AML and MM were in common with sCD86 levels in AML patients, not obviously correlated to other clinical and prognostic parameters. It is presently unknown whether mCD86 expression by these malignant cells plays a direct role in tumour progression or is solely a marker of inherently more aggressive or treatmentresistant tumours.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Many haematological malignancies express B7 constitutively 8 and in both AML and multiple myeloma (MM) patients membrane expression of CD86 is in fact associated with a considerably poorer prognosis. 9,10 The levels of mCD86 in AML and MM were in common with sCD86 levels in AML patients, not obviously correlated to other clinical and prognostic parameters. It is presently unknown whether mCD86 expression by these malignant cells plays a direct role in tumour progression or is solely a marker of inherently more aggressive or treatmentresistant tumours.…”
Section: Discussionmentioning
confidence: 98%
“…8 Recent studies have shown that CD86 expression by malignant cells is in fact associated with a poor prognosis in both acute myeloid leukaemia (AML) and multiple myeloma (MM). 9,10 A broad range of leukocyte cell surface antigens are released as soluble forms, many of which have agonistic, antagonistic or independent biological effects relative to their membrane bound counterparts. [11][12][13] Studies of in vivo soluble forms of B7 have, however, been limited.…”
Section: Introductionmentioning
confidence: 99%
“…In a recent study, B7.2 positive AML was associated with a poor prognosis. 99 These results need further confirmation, but they may indicate that B7.2 expression is associated with other functional characteristics which are prognostically dominant to an increased immunostimulatory capacity.…”
Section: Expression Of B71 (Cd80) and B72 (Cd86) By Aml Blastsmentioning
confidence: 92%
“…Clinical studies in allogeneic bone marrow transplant recipients Increased risk of leukemia relapse, decreased risk of GVHD and transplant-related mortality in identical twin transplants 10 Complete remission has been observed after treatment of post-transplant AML relapse with donor leukocyte transfusions [12][13][14][15][16][17] The frequencies of host reactive helper and cytotoxic T lymphocytes in stem cell donors correlate with the risk of GVHD 23,24 Cytotoxic T cells recognizing minor histocompatibility antigens can inhibit AML blast proliferation 27 AML blasts expression of membrane molecules necessary for antigen-specific T cell activation AML blasts express HLA class I and class II molecules which are capable of presenting processed antigenic peptides [29][30][31][32][33][34][35][36][37][38][39][40] AML blasts express molecules mediating costimulatory signals (LFA-3, ICAM-1, B7.1, B7.2) effects during antigen-specific T cell activation 29,71,[99][100][101][102][103][104] Normal T cell recognition of leukemia-specific antigenic peptides…”
Section: Clinical Evidence For Antileukemic T Lymphocyte Reactivitymentioning
confidence: 99%
“…For example, CD56 expression in AML with t(8;21) is associated with a significantly shorter duration of CR and survival (17). B7-2 is one of the most crucial factors in the prognosis of adult acute leukemia and has an important role in tumor immunity (18), and poliovirus receptor-related (PRR) proteins could play a role in leukemia. Patients with a high level of PRR1 or PRR2 expression exhibit a more favorable prognosis (19).…”
Section: Deficient Immunity and A Lack Of Dcs In Patients With Leukemiamentioning
confidence: 99%